Quantitation of chemotactic factor generation in human sera - Tannous, R; Cavender, N (Journal of immunological methods, 1980)
Increased sensitivity of chemotaxin titration in the 'migration under agarose' method was achieved by reduction in agarose concentration of the medium from the conventional 1.0% to 0.5%. Satisfactory technical properties of the gel were achieved by inclusion of 2.0% bovine serum albumin. The modificatin resulted in increased migration rates and greater reproducibility than those achieved with other media. The range of normal values was established by study of sera of 20 normal adults with use of a single batch of target cells. It is concluded that under the conditions described, a difference in chemotactic differential of 10% or more between a serum sample submitted for assay and that of pooled serum from normal subjects is statistically significant.